2019
DOI: 10.1111/jvim.15493
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of microbial dysbiosis, fecal unconjugated bile acid concentrations, and disease activity in dogs with steroid‐responsive chronic inflammatory enteropathy

Abstract: Background Mounting evidence from human studies suggests that bile acid dysmetabolism might play a role in various human chronic gastrointestinal diseases. It is unknown whether fecal bile acid dysmetabolism occurs in dogs with chronic inflammatory enteropathy (CE). Objective To assess microbial dysbiosis, fecal unconjugated bile acids (fUBA), and disease activity in dogs with steroid‐responsive CE. Animals Twenty‐four healthy control dogs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
104
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(113 citation statements)
references
References 33 publications
7
104
2
Order By: Relevance
“…The DI is the first tool that allows quantification of gut dysbiosis, and can be used to monitor dysbiosis over time and in response to treatment. Other studies have since confirmed that DI is increased in dogs with CE (26,27,82).…”
Section: Gut Microbiome and Gi Diseasesmentioning
confidence: 81%
See 4 more Smart Citations
“…The DI is the first tool that allows quantification of gut dysbiosis, and can be used to monitor dysbiosis over time and in response to treatment. Other studies have since confirmed that DI is increased in dogs with CE (26,27,82).…”
Section: Gut Microbiome and Gi Diseasesmentioning
confidence: 81%
“…Interestingly, one of the Clostridiaceae strains was later identified as Clostridium hiranonis, a bacterial species associated with normal bile acid (BA) metabolism (25,26). A study (23) reported normal BA metabolism in healthy dogs fed BARF diets, with no significant difference from kibble-fed controls.…”
Section: The Effect Of Dietmentioning
confidence: 99%
See 3 more Smart Citations